A comparative analysis of radiographer versus radiologist in the diagnosis of rotator cuff tears of the shoulder using ultrasound - Hakim ZA; Ali S; Bale RS; Hughes PJ (Orthopedic Research and Reviews, 2015)
Zuned A Hakim, Syed Ali, R Stephen Bale, Peter J HughesTrauma and Orthopaedic Department, Royal Preston Hospital, Preston, UK Introduction: Rotator cuff pathology is a commonly encountered shoulder complaint, which is routinely investigated with ultrasound scan. Sensitivities and specificities for detecting tears have been reported to be between 79% and 100%. Our aim was to compare the scans performed by a radiographer versus a radiologist with that of surgery. Patients and methods: This study is a retrospective review of 184 cases over a 12-month period who underwent arthroscopy following an ultrasound scan for cuff disease. Single clinician collected data for cuff pathology based on the scan report and compared to intraoperative findings. StatsDirect was used for statistical analysis to determine sensitivities, specificities, and accuracy. Results: The radiologist had better sensitivity for partial-thickness tears by 33% (95% CI 4.4%–59.9%, P=0.018). The radiographer had better specificity by 24% (CI 11.9%–38.8%, P=0.0001). The radiographer had better accuracy at 55% versus radiologist at 23% and was better at quantifying the size of the tear. Intraoperative change in the plan occurred in 15% of cases in each group. Discussion: Our findings for specificity, sensitivity, and accuracy for full-thickness tears are comparable to the existing literature, but lower than most of the quoted papers for partial-thickness tears. Change in intraoperative plan as a result of differing findings at surgery is equal in each group. We found the radiographer to be better at sizing the full-thickness tears. Keywords: rotator cuff, ultrasound, accuracy difference